2021
DOI: 10.3389/fimmu.2020.620374
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell-Based Immunotherapy in Lung Cancer

Abstract: Lung cancer remains the leading cause of cancer-related death worldwide. The advent of immune checkpoint inhibitors has led to a paradigm shift in the treatment of metastatic non-small cell and small cell lung cancer. However, despite prolonged overall survival, only a minority of the patients derive clinical benefit from these treatments suggesting that the full anti-tumoral potential of the immune system is not being harnessed yet. One way to overcome this problem is to combine immune checkpoint blockade wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 120 publications
(121 reference statements)
0
40
0
Order By: Relevance
“…First, very recently, Zhou et al suggested that LT3 could be repositioned for cancer immunotherapy based on its ability to block the T Cell Immunoreceptor with Ig and ITIM domains (TIGIT)/poliovirus receptor (PVR) interaction—an emerging immune checkpoint system [ 135 ]. Second, the ability of LT3 to induce phenotypic and functional activation of DCs [ 23 ] could potentiate the promising dendritic cell-based immunotherapy in lung cancer [ 136 ]. Third, preliminary in vitro data have suggested that pretreatment with LT3 or administration of LT3 during chemotherapy could reinforce the efficacy of chemotherapy—a promising strategy known as “choriocarcinoma-mimic chemotherapy”, or “neo-endocrinochemotherapy”.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…First, very recently, Zhou et al suggested that LT3 could be repositioned for cancer immunotherapy based on its ability to block the T Cell Immunoreceptor with Ig and ITIM domains (TIGIT)/poliovirus receptor (PVR) interaction—an emerging immune checkpoint system [ 135 ]. Second, the ability of LT3 to induce phenotypic and functional activation of DCs [ 23 ] could potentiate the promising dendritic cell-based immunotherapy in lung cancer [ 136 ]. Third, preliminary in vitro data have suggested that pretreatment with LT3 or administration of LT3 during chemotherapy could reinforce the efficacy of chemotherapy—a promising strategy known as “choriocarcinoma-mimic chemotherapy”, or “neo-endocrinochemotherapy”.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…Conventional production processes of DC vaccines involve TAAs after a comprehensive and individualized TAA selection. 20 However, we enforced DCs with killed human adenocarcinoma cell lines during manufacturing, with the ability to recognize full antigens of human adenocarcinoma cells. Our procedure increased the possibility of provoking a stronger tumor-directed immune response, and was at the same time more practical as individualized antigen selection was no longer necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical administration of DC vaccines is first achieved by using leukapheresis to harvest monocytes from peripheral blood. Subsequently, immature and mature DCs are generated through culturing with IL-4 and GM-CSF and are then exposed to activating factors for maturation [109]. Next, a tumor biopsy is taken from the patient, after which TAA mRNA or total tumor mRNA is electroporated into mature DCs.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Next, a tumor biopsy is taken from the patient, after which TAA mRNA or total tumor mRNA is electroporated into mature DCs. The resulting antigenloaded DCs are then cryopreserved and injected back into the patient [109]. In this process, it is evident that DC vaccines are a considerably expensive and difficult treatment modality to produce, which is one of its main drawbacks.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%